Conventional Electrode Materials for Microbial Fuel Cells - Rabia Tasaduq, Hussain; Khalid, Umar; Akil, Ahmad; Showkat, Ahmad Bhawani; Mohammed B., Alshammari (Springer Singapore, 2022)
The use of microbial fuel cells (MFCs) has gained a lot of attention as a means to combat both energy shortages and water pollution. Despite their best efforts, MFCs are unable to produce substantial amounts of energy or effectively remove pollutants due to a number of difficulties, one of which being the electrode. One of the most significant components of an MFC is the electrode. Different types of electrode materials have recently been developed to boost pollutant removal rates and energy production efficiency. Carbon-based materials have been used as the most often used electrode material in MFCs. A wide range of potentials is now accessible for use in the manufacturing of electrode materials, which can significantly reduce current issues such as the demand for high-quality materials and their cost. In the present chapter, the conventional electrode material is briefly discussed with their influence and role in MFC operation and performance. A brief discussion of the current issues and future views of electrode materials is also included.